PEMANFAATAN SUMBER DAYA ALAM DENGAN MENGGUNAKAN BATANG ROTAN SEBAGAI PENGGANTI TULANGAN BETON - Irma Wirantina Kustantrika (Sekolah Tinggi Teknik - PLN, 2016)
Iron ore as a raw material of steel reinforcement in concrete can not endeavor to increase production because it is a natural resource that is not renewable. To overcome dependence consumption of reinforcing steel in the concrete is then used altrenatif other material as the reinforcing steel that is easy, inexpensive to obtain and resistant to corrosion, namely in the form of reinforcement of rattan sticks. It is intended that the natural resources we have can be reused to the maximum. This study uses a cane kind seel as reinforcement concrete beams. Tests conducted by the method of loading one point, cracks are expected in this test is failed bending. Reinforcement made from 1 piece of iron reinforcement and 2 rattan wrapped reinforcement wire reinforcement bendrat round face, it is expected that the adhesion reinforcement with concrete stronger. Testing was done by testing reinforced concrete beam flexural capacity using a type of reinforcement rattan cane plain size OD OD 20 mm and 30 mm. With the quality of the concrete used for fc '= 18.675 MPa. The test specimen concrete beam flexural capacity was only 28 days with the test method fourth point loading system.